Description of two new species of the genus Glyphiulus Gervais, 1847 (Diplopoda: Spirostreptida: Cambalopsidae) from southern China - Jiang, Xuan-Kong; Chen, Hui-Ming; Xie, Zhi-Cai (Zootaxa, 2022)
Two new species of the millipede genus Glyphiulus Gervais, 1847 are described from southern China: Glyphiulus fortis sp. nov. and Glyphiulus hainanensis sp. nov. Glyphiulus fortis sp. nov. is cavernicolous, vs. G. hainanensis sp. nov. which was collected from an epigean environment. Both of them belong to the G. javanicus-group. Additionally, DNA barcoding and phylogenetic analyses based on nucleotide sequences of COI and 16S of the two new species, as well as their allied species were conducted. The morphological characteristics, the genetic distances and the phylogenetic tree revealed that the two new species are unambiguously distinct from their congeners.